2004
DOI: 10.1089/jmf.2004.7.408
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hydrogen Peroxide-Induced Endothelial Apoptosis by 2′,4′,7-Trihydroxyflavanone, a Flavonoid Form

Abstract: Oxidative stress contributes to cellular injury following clinical and experimental ischemia/reperfusion episodes. Oxidative injury can induce cellular and subcellular damage that results in apoptotic cell death. We tested whether 2',4',7-trihydroxyflavanone, a synthetic flavonoid derivative, inhibits hydrogen peroxide (H(2)O(2))-induced toxicity in human umbilical endothelial cells (HUVECs). Cultured HUVECs were incubated for 30 minutes with 0.2 mM H(2)O(2) in the absence and presence of 2',4',7-trihydroxyfla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…H 2 O 2 is also quickly converted to toxic HOCl species. It is well known that H 2 O 2 -mediated oxidative stress can cause cell death [ 31 , 32 ]. We tested whether ENT could inhibit H 2 O 2 -induced toxicity in HUVECs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 O 2 is also quickly converted to toxic HOCl species. It is well known that H 2 O 2 -mediated oxidative stress can cause cell death [ 31 , 32 ]. We tested whether ENT could inhibit H 2 O 2 -induced toxicity in HUVECs.…”
Section: Resultsmentioning
confidence: 99%
“…For example, high levels of ROS-mediated oxidative stress can damage the structure and functions of endothelial cells, and contribute to pathogenesis of hypertension, diabetes, inflammation and atherosclerosis [ 58 , 59 ]. The assays of H 2 O 2 -induced death of endothelial cells or neuronal cells are commonly used in vitro models for determining antioxidant effects on oxidative stress [ 31 , 32 , 60 , 61 ]. Using these assays, other have shown that H 2 O 2 is highly permeable to cell membrane [ 62 ] and can increase production of O 2 − by activating NADPH oxidase and eNOS uncoupling [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 Their extensive spectrum of biological activities has attracted considerable interest in medicinal chemistry and in organic synthesis. Indeed, chalcones have been shown to exhibit anticancer, 1−3 antiinflammatory, 4 antioxidant, 5 antifungal, 6 and antibacterial 7 activities. Therefore, a number of synthetic methods have been reported for the synthesis of these valuable derivatives, among which aldol and ClaisenSchmidt condensations are currently the common and simple protocols toward chalcones.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the anticancer activity of these synthetic compounds has been observed in various cancer cell lines in vitro (Liu et al, 1992;Min et al, 1997;Choi et al, 2004;Ying et al, 2008). We previously reported the production of synthetic flavonoids (Lee and Jung, 2005;Lee et al, 2007;Lee, 2008) that exert various biological activities in vitro (Choi et al, 2010) and have since been examining the phytoceutical applications of synthetic flavanone derivatives.…”
Section: Introductionmentioning
confidence: 99%